Efektivitas dan Efisiensi Penggunaan Faktor Produksi Usahatani Kangkung Pada Kelompok Tani Setia Tani di Desa Ciaruteun Ilir, Kecamatan Cibungbulang, Kabupaten Bogor - JENICA, IRENA DEA; WIDHIANTHINI, WIDHIANTHINI; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
The Effectiveness and Efficiency of the Use of Production Factors for Water Spinach Farming in Setia Tani Farmer's Group in Ciaruteun Ilir Village, Cibungbulang District, Bogor Regency The agricultural production process is driven by the fulfillment of production factors needs. Lacking of production factors can affect farm production. This condition requires farmers to use production factors effectively and efficiently. This study aims to analyze the effect, effectiveness and efficiency of production factors. Data were obtained through interviews with questionnaires to 52 farmers. The research analysis used Cobb-Douglas analysis which was processed using SPSS software. The results showed that the use of water spinach production factors together had an effect on water spinach production. In the other hand, manure and urea were not partially significant. Meanwhile, land area, labor, and seeds have a significant effect. The use of production factors has not yet reached the effective and efficient level. This can be seen from effectiveness level by comparing the MPP and APP values which are only around 6.3-42.6%. The analysis result of the efficiency of labor variable and the use of manure are inefficient so that their use must be reduced. Meanwhile the area of land, seeds, and urea fertilizer is not yet efficient, meaning that the use of production factors must be increased in terms of the NPM/Px value.